EFFECT OF TOURISM PRODUCT AND TOURISM PROMOTION ON INTEREST IN VISITING TOURIST ATTRACTIONS - Syech Idrus; I Wayan Gede Antok Setiawan Jodi; Latif Latif; Luh Komang Candra Dewi; Syamsulbahri (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine and analyze effect of tourism product and tourism promotion on interest in visiting tourist attractions. This research is descriptive research with a quantitative approach. Population is tourists who are or have made tourist visits in Medan City. Sampling method used in this study is a sampling method based on convenience. Sample that will be required is 100 to answer the questionnaire so that the answers obtained are more representative. This study uses multiple linear regression model. The results show that tourism product has a positive and significant effect on interest in visiting tourist attractions. Tourism promotion has a positive and significant effect on interest in visiting tourist attractions.